Revised Ordinances of the City of Fort Worth, Texas, 1873-1884, at 64-65, An Ordinance prohibiting the shooting off, firing or discharging of Fire-arms; the firing, exploding or setting off of Squibs, Firecrackers, Torpedoes, Roman Candles, Sky-rockets or other things containing powder or other explosive matter, or the throwing of any fire balls, or making of any bon-fires in the corporate limits of the City of Fort Worth. Be it ordained by the City Council of the City of Fort Worth: § 1 (1885) - (:unkn) unknown (General Publisher, 1880)
It shall be unlawful for any person or persons to shoot off, fire, or discharge any gun, pistol, revolver or any firearm of any description, or to fire, explode or set off any squib, firecracker, torpedo, roman candle, sky-rocket, or other thing containing powder or other explosive matter, or to throw any fire-ball or make any bon-fire in the corporate limits of this city
--
Keywords: DISCHARGE